PENINGKATAN DAYA SAING BISNIS KLASTER “KARYA BOGA” MELALUI SISTEM PENJUALAN BERBASIS E-COMMERCE - Nugroho Agung Prabowo; Retno Rusdjijati; Oesman Raliby (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2012)
Magelang’s snacks cluster, “Karya Boga”, are still experiencing so many obstacles in marketing the products. The members mostly sell the product individually by offering and delivering the products directly to the customers. Therefore, the sales areas are limited, hence, the product is not known in larger scales. One of sales methods can be used to overcome this problem is on-line sales in the form of e-commerce. Nevertheless, not many cluster members know e-commerce, so that it takes a research to figure out the members’ levels of understanding and motivation on e-commerce use. After the members’ levels of understanding and motivation on e-commerce use are figured out, the next step is designing the sales system of the cluster’s product by using e-commerce. The result of the research shows that the members’ level of understanding or the level of e-commerce adoption is medium, and the variation is low. This is caused by the limited number of human resources who are able to use IT. Nevertheless, they are highly motivated in applying IT to sell their products. The motivation is there because of the members’ wish to seek new customers and to raise their income. Next, e-commerce is designed by using Content Management System (OMS) prestashop.